Couples-based approach to HIV prevention for transgender women and their partners: study protocol for a randomised controlled trial testing the efficacy of the 'It Takes Two' intervention. Issue 10 (15th October 2020) - Gamarel, Kristi E; Sevelius, Jae M; Neilands, Torsten B; Kaplan, Rachel L; Johnson, Mallory O; Nemoto, Tooru; Darbes, Lynae A; Operario, Don
Abstract : Introduction: HIV transmission and acquisition risk among transgender women is particularly high in the context of primary partnerships. This project extends a previous pilot couples-focused HIV intervention programme, which was shown to be feasible, acceptable and promising in reducing sexual risk behaviour among transgender women and their partners. This randomised controlled trial (RCT) tests the efficacy of this culturally sensitive HIV prevention programme for HIV-serodiscordant and HIV-negative seroconcordant transgender women and their partners. Methods and analysis: To finalise the protocol for trial, we used qualitative methods to hone eligibility criteria, refine the intervention and control manuals, and name and brand the intervention ('It Takes Two'). The RCT investigates the effects of the It Takes Two intervention on Composite Risk for HIV (CR-HIV) among 100 couples. CR-HIV is a binary indicator of couple HIV risk using validated measures of sexual behaviour, pre-exposure prophylaxis use among HIV-negative participants and viral suppression among participants living with HIV. Using a two-arm RCT, we will examine intervention effects on CR-HIV at 12-month follow-up comparing transgender women and their partners randomised to the intervention versus control (HIV prevention information only). Ethics and dissemination: This study has been reviewed and approved by the University of California, San Francisco (19-28624) and the University of Michigan (HUM00147690) Institutional Review Boards. Participants provide informed consent before taking part of the study activities. Results will be published in peer-reviewed journals and presented at scientific conferences. We will make our results available to the community of researchers and general public interested in transgender health to avoid unintentional duplication of research, as well as to others in the health and social services community, including LGBT community-based organisations, AIDS service organisations and other transgender-serving organisations. The full de-identified dataset and codebook will be shared at the University of Michigan Digital Repository. Trial registration number: NCT04067661 .